Sport for Sustainable Development Historical and Theoretical Approaches - Hozhabri, Kazem; Sobry, Claude; Ramzaninejad, Rahim (Springer International Publishing : Imprint: Springer, 2022)
VII, 96 p. 2 illus., 1 illus. in color.